STRUCTURAL AND MORPHOLOGICAL INVESTIGATION OF FUNCTIONALIZED REDUCED GRAPHENE OXIDE-MULTI WALLED CARBON NANOTUBES NANOCOMPOSITE - Upadhyay, Chandramani; Shahzad, Hanzala; Javid, Mehreen; Soni, Bhumika; Ahmad, Tameem; Azmi, Kashif; Ali, Md Arshad; Ali, Firdaus (Indonesian Physical Review, 2020)
2D materials like Graphene and its composite has emerged as most valuable and major concern because of their peculiar properties in field of nanotechnology in past few decades. Herein, we report the effective technique for the synthesis of functionalized r-GO/MWCNTs nanocomposite using probe sonication. The synthesized samples were tested via XRD, FESEM, FTIR and Raman Spectroscopy. X-ray diffraction technique was used for the structural analysis of the samples which revealed that most prominent peak was observed around 2Î¸~26Â°. Surface morphology of the samples were studied via FESEM, which revealed that r-GO layers were wrapped around the MWCNTs. Raman spectra were recorded for the determination of quality of r-Go and MWCNT via the position and intensity of D and G band. The various functionalities present on the samples were identified via FTIR spectra.